Insulin resistance and its role in the pathogenesis of pre-diabetes development in obese adolescents - Nadezhda B. Min'kova; Oleg Iu. Latyshev; Goar F. Okminyan; Elena V. Kiseleva; Dar'ia S. Romaikina; Liubov N. Samsonova (Consilium Medicum, 2023)
Background. The prevalence of childhood obesity has increased significantly over the past three decades worldwide, and in this regard, the frequency of diseases associated with obesity, including disorders of carbohydrate metabolism, has increased. The involvement of insulin resistance and insulin deficiency in the development of prediabetes in obesity has been established. However, the significance of each pathological mechanism in the development of prediabetes in childhood and adolescence has not been established. In this regard, in children's practice, there is no reliable data on methods of prevention and treatment of prediabetes in obesity.